2015
DOI: 10.1186/s12936-014-0525-y
|View full text |Cite
|
Sign up to set email alerts
|

In vivo antiplasmodial and toxicological effect of Maytenus senegalensis traditionally used in the treatment of malaria in Tanzania

Abstract: BackgroundIn Tanzania and elsewhere, medicinal plants, including Maytenus senegalensis, are still widely used in the treatment of malaria and other ailments. The aim of the present study was to investigate the in vivo antiplasmodial and toxic effects in mice.MethodsOral antiplasmodial and acute toxicity of the ethanolic root extract of M. senegalensis was evaluated in mice. The Peters 4-day in vivo antiplasmodial effect against early rodent malaria infection in chloroquine-sensitive Plasmodium berghei NK 65 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 19 publications
0
30
0
1
Order By: Relevance
“…Thus, we could say that leaves of M. gracilipes possessed antimalarial activity. This assertion is further evidenced by in vivo study that reported antiplasmodial activity of other species of the same genus Maytenus senegalensis [ 60 ]. Malaria is frequently treated with drugs that have antibacterial properties.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, we could say that leaves of M. gracilipes possessed antimalarial activity. This assertion is further evidenced by in vivo study that reported antiplasmodial activity of other species of the same genus Maytenus senegalensis [ 60 ]. Malaria is frequently treated with drugs that have antibacterial properties.…”
Section: Discussionmentioning
confidence: 76%
“…The involvement of local communities in the design and implementation of schistosome and intestinal worm control programmes is increasingly becoming recognized as crucial if cost-effective and long-term success is to be realized. Despite criticisms [ 30 ], PHAST approach is still useful in empowering communities to control water, hygiene, and sanitation-related infectious diseases such as schistosomiasis and intestinal worm infections. Once people’s knowledge and perceptions of the disease and its consequences are recognized, health education needs to be tailored to enhance more understanding of the nature of the disease and the human role in its transmission.…”
Section: Discussionmentioning
confidence: 99%
“…These were (+)-catechin and caffeic acid. Hamisi et al [119] found that the ethanolic extracts of root barks of M. senegalensis possessed potent anti-plasmodial effects, and may, therefore, serve as a potential source of an alternative safe, effective and affordable anti-malarial drug. Bishnoi [120] studied the anti-hyperglycemic activity of the hydroalcoholic extracts of the leaves of M. emarginatus.…”
Section: Other Pharmacological Activitiesmentioning
confidence: 99%